The Alpine LGM in the boreal ice-sheets game - Monegato, Giovanni; Scardia, Giancarlo [UNESP]; Hajdas, Irka; Rizzini, Francesca; Piccin, Andrea (Nature Publishing Group, 2017)
New chronologic and stratigraphic constraints from the Garda morainic amphitheater define the extension of the last glaciation in the Adige-Sarca system and improve the Alpine LGM dataset. Together with the available chronology of the Rhine and Tagliamento systems, our results indicate a synchronous maximum culmination of Alpine glaciers during the LGM, which anticipated by about 3.5 ka the maximum extension of the Eurasian Ice Sheet (EIS). This is ascribed to the sensitivity of Alpine glaciers to the availability of moisture from southerly circulation, as recently documented by speleothem delta O-18 curve from Sieben Hengste (7 H). According to global circulation models, the waxing of the North American Ice Sheet (NAIS) at 26-23 ka pushed the North Atlantic jet stream southwards. This enhanced precipitation rates in southern Europe by advection of moisture from the Mediterranean Sea, triggering expansion of the Alpine glaciers. NAIS waning after 23 ka led to the gradual re-establishment of westerly circulation and renewal of a moisture supply to northern Europe, feeding the EIS to its maximum volume. Reduced supply of moisture from the Mediterranean Sea sealed the fate of the Alpine glaciers, which entered a final recessional phase after 22 ka and faded out after 17.5 ka.